2010
DOI: 10.1007/s12274-010-0002-z
|View full text |Cite
|
Sign up to set email alerts
|

Palladium nanoparticle-graphene hybrids as active catalysts for the Suzuki reaction

Abstract: Graphene has been successfully modified with palladium nanoparticles in a facile manner by reducing palladium acetate [Pd(OAc) 2 ] in the present of sodium dodecyl sulfate (SDS), which is used as both surfactant and the reducing agent. The palladium nanoparticle-graphene hybrids (Pd-graphene hybrids) are characterized by highresolution transmission electron microscopy, atomic force microscopy, Raman spectroscopy, X-ray photoelectron spectroscopy, X-ray diffraction, and energy dispersive X-ray spectroscopy. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
194
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 288 publications
(199 citation statements)
references
References 49 publications
4
194
0
1
Order By: Relevance
“…Zhang et al [178] successfully synthesized Pd NPgraphene hybrids in a facile manner by reducing palladium acetate (Pd(OAc) 2 ) in the presence of sodium dodecyl sulfate (SDS), which was used as both surfacant and reducing agent. They demonstrated that the Pd NP-graphene hybrids can act as efficient catalysts for Suzuki reaction under aqueous and aerobic conditions, with the reaction reaching completion in 5 min.…”
Section: C-c Coupling Reactionsmentioning
confidence: 99%
“…Zhang et al [178] successfully synthesized Pd NPgraphene hybrids in a facile manner by reducing palladium acetate (Pd(OAc) 2 ) in the presence of sodium dodecyl sulfate (SDS), which was used as both surfacant and reducing agent. They demonstrated that the Pd NP-graphene hybrids can act as efficient catalysts for Suzuki reaction under aqueous and aerobic conditions, with the reaction reaching completion in 5 min.…”
Section: C-c Coupling Reactionsmentioning
confidence: 99%
“…These Pd/G catalysts exhibited quite good efficiencies for Suzuki reaction, under aqueous as well as aerobic conditions, in a very short time span. 47 Recently, a number of research groups have successfully explored the potential of Pd/GO/G catalysts in facile Suzuki coupling reactions. [48][49][50][51] In yet another work, Gao and coworkers utilized Au/GO nanocomposites, which showed unusually high activities for SuzukiMiyaura coupling reaction of chlorobenzene and phenylboronic acid.…”
Section: +2mentioning
confidence: 99%
“…Se han explorado materiales híbridos como grafeno dopado con metales nobles para este propósito, sin embargo, estos metales están limitados por su escasa disponibilidad y el elevado costo, [4,5,6]. En este contexto, los metales de transición pueden servir como una alternativa prometedora [7,8,9]. En la búsqueda de nuevos materiales catalíticos los métodos computacionales de primeros principios han demostrado ser útiles herramientas en el diseño racional de catalizadores ya que permiten llegar a resultados y tendencias comparables con datos experimentales, de un modo relativamente rápido, [10].…”
Section: Introductionunclassified